Modified organic composite bentonite, and preparation method and application thereof
Patent Information
- Application Number
- CN202410262248.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-07
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-03-07
AI Technical Summary
[0005]膨润土有机插层改性在废水处理等领域已有广泛应用,但在铁矿球团领域的相关研究较少,研究手段单一且不具体,对插层机理层面的研究较少,有机改性膨润土在铁矿球团领域的实际应用中受到了限制
[0023](1)本发明创新地发现添加迁移助剂(二甲基亚砜)可有效促进有机粘结剂的分散,首先水溶液与迁移助剂搅拌混合进行第一反应,随后再与有机粘结剂混合后添加到膨润土中进行陈化第二反应,采用酒精为介质对第二反应陈化后的膨润土进行湿磨,通过机械力的机械能活化作用与迁移助剂的介导作用协同处理来完成第三反应;干燥后研磨过筛即得;基于上述反应思路,进一步配合各条件/参数的控制,能够较好地实现协同;更重要的是,采用该方法获得的改性有机复合膨润土在铁矿球团领域具有意料不到的优势。
Smart Images

Figure CN118125460B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of iron ore pelletizing technology, and particularly to a modified organic composite bentonite, its preparation method, and its application. Background Technology
[0002] Bentonite is the most important binder in iron ore pellet production. my country has abundant bentonite reserves, but most are low-quality calcium-based bentonite. High-quality natural sodium-based bentonite reserves are scarce and insufficient to meet demand. The development and utilization of organic bentonite is limited by technological limitations, production equipment, and the high cost of surfactants. High-end bentonite products still rely on imports. These problems urgently need to be addressed. To fully utilize domestic bentonite resources, it is necessary to strengthen research on bentonite upgrading and modification to develop high-performance bentonite products with high economic benefits. Currently, bentonite upgrading and modification mainly includes sorting and purification, sodium modification, and organic modification. Among these, organic modification is the mainstream direction for bentonite upgrading and modification.
[0003] The key to organic modification lies in the selection of organic binders and modification processes. The organic chain should have a spatial network structure, with branches containing both hydrophilic and polar groups. Through theoretical calculations and experiments, scholars have proposed an ideal molecular configuration for organic binders and established that the polar and hydrophilic groups in organic binders are -COO- and -OH, respectively.
[0004] Bentonite's main component is montmorillonite, a 2:1 layered crystal structure consisting of two layers of Si-O tetrahedra sandwiching a layer of Al-O octahedra. It possesses excellent cation exchange capacity, adsorption capacity, water absorption, and suspension properties. The montmorillonite unit layers are connected by forces, resulting in a relatively loose interlayer structure that allows water and other molecules to penetrate. Adding organic reagents to the montmorillonite interlayers can improve its adsorption and water absorption, enabling modified bentonite to meet the needs of various fields.
[0005] Organic intercalation modification of bentonite has been widely used in wastewater treatment and other fields, but related research in the iron ore pelletizing field is limited. Research methods are often simplistic and lack specificity, with insufficient study on the intercalation mechanism. This restricts the practical application of organically modified bentonite in iron ore pelletizing. Currently, in-depth research has not been conducted on issues such as the selection of intercalating agents and the improvement of intercalation techniques. Summary of the Invention
[0006] This invention provides a modified organic composite bentonite, its preparation method, and its application, with the aim of solving the aforementioned problems existing in the background art.
[0007] To achieve the above objectives, embodiments of the present invention provide a modified organic composite bentonite, its preparation method, and its application. The preparation method is simple to operate and low in cost. The prepared organic modified bentonite has good hydrophilicity and dispersibility, and can be used as an excellent binder in the field of iron ore pelletizing.
[0008] An embodiment of the present invention provides a method for preparing modified organic composite bentonite, comprising the following steps:
[0009] S1: Mix the migration aid with water and stir, then add the organic binder, heat and disperse evenly to obtain a mixed solution;
[0010] S2: Add the mixed solution to bentonite and mix well to obtain a mixture, then carry out an aging reaction;
[0011] S3: The mixture after the reaction is subjected to wet ball milling, dried, ground and sieved to obtain the final product.
[0012] Preferably, in step S1, the migration aid is dimethyl sulfoxide, a polar organic small molecule with a large dipole moment, containing the functional group -S=O- which can accept protons and form hydrogen bonds with Al-OH between montmorillonite layers, and is adsorbed between montmorillonite layers; the organic binder is at least one of humic acid (HA), carboxymethyl cellulose (CMC), polyacrylamide (PAM), carboxymethyl starch (CMS), and polyvinyl chloride (PVC).
[0013] Preferably, in step S1, the mass ratio of migration aid to water is 0.5 to 1.0; the mass percentage of migration aid in bentonite is 0.01 to 12%; and the mass percentage of organic binder in bentonite is 0.1 to 10%.
[0014] Preferably, in step S1, the heating temperature is 80°C. Heating is used to treat organic binders that are difficult to dissolve in solution to promote their dissolution.
[0015] Preferably, in step S2, the aging reaction time is 24–36 hours.
[0016] Preferably, in step S3, the wet ball milling process specifically involves using a planetary ball mill with 95% ethanol as the medium for wet ball milling.
[0017] Preferably, in step S3, the wet ball milling time is 20-30 min and the wet ball milling speed is 300-400 r / min.
[0018] Preferably, in step S3, the sieving process specifically involves passing the material through a 200-mesh sieve and collecting the material that passes through the sieve.
[0019] Based on a general inventive concept, embodiments of the present invention provide a modified organic composite bentonite obtained by the above-described preparation method.
[0020] The embodiments of the present invention also provide an application of the modified organic composite bentonite obtained by the above preparation method or the above modified organic composite bentonite in iron ore pellets.
[0021] This invention modifies organic composite bentonite using mechanical force and enhances its effectiveness by adding dimethyl sulfoxide, a small-molecule migration aid. Compared to traditional organic modification of bentonite, this method effectively improves the performance of modified bentonite and reduces the amount of bentonite used in iron ore pellet production. Traditional organic modification of bentonite using organic binders typically involves simply mixing and aging the organic binder with bentonite before use. The oxygen-containing functional groups, such as hydroxyl and carboxyl groups, in the organic binder are adsorbed onto the bentonite surface. In the preparation of iron ore pellets, this strengthens the bond between the organically modified bentonite and the iron concentrate, while simultaneously increasing the hydrophilicity of the iron concentrate surface, thereby improving green pellet strength and reducing the amount of bentonite required. However, the adsorption of organically modified bentonite onto iron ore mainly occurs through electrostatic adsorption, hydrogen bonding, and chemical adsorption. The disadvantages of this modification method are the large amount of organic binder required, difficulty in achieving uniform mixing with bentonite, and poor stability. The enhanced adhesion is primarily achieved through the synergistic effect of the organic binder and bentonite's bonding properties, without any substantial improvement in the quality of the bentonite itself. This invention utilizes the synergistic effect of mechanical force and small-molecule migration aids. Under the activation effect of mechanical energy, the particle size of bentonite decreases, the specific surface area increases, and particle fracture disrupts its stable crystal structure. This leads to lattice distortion and reduced grain size in bentonite, enhancing the negative potential and reducing electronegativity of the bentonite surface. The number of active sites and adsorption energy on the particle surface increases, promoting the insertion of small-molecule organic binders into the montmorillonite interlayer. Chemical reactions and hydrogen bond adsorption occur on the end faces and basal surfaces of the montmorillonite. Furthermore, the mechanical activation and the mediation effect of the migration aids further enhance the bonding effect. The -S=O- group in the migration aid dimethyl sulfoxide forms hydrogen bonds with the Al-OH groups in the montmorillonite interlayer, acting as a carrier to strengthen the binding of the organic binder with bentonite, improving the dispersibility of the organic binder in the bentonite, and further promoting the effective insertion of some small organic molecules into the montmorillonite interlayer. This results in even lower electronegativity on the bentonite surface, thus achieving highly efficient organic intercalation modification of bentonite. Modified organic composite bentonite, enhanced by the synergistic effect of mechanical energy and mediation, possesses advantages such as excellent physicochemical properties, strong hydrophilicity, good dispersibility, outstanding bonding effect, and low dosage. When used in the preparation of iron ore pellets, it can form a more stable "carousel-like" gel structure within the pellets, enhancing the bonding strength between bentonite and iron concentrate. This invention not only improves the physicochemical properties of bentonite itself and effectively reduces the amount of bentonite used, but also promotes the improvement of pellet performance.
[0022] The above-described solution of the present invention has the following beneficial effects:
[0023] (1) This invention innovatively discovers that adding a migration aid (dimethyl sulfoxide) can effectively promote the dispersion of organic binders. First, the aqueous solution is stirred and mixed with the migration aid to carry out the first reaction. Then, it is mixed with the organic binder and added to bentonite for the second reaction of aging. The bentonite after the second reaction is wet-milled using alcohol as a medium. The third reaction is completed through the synergistic treatment of the mechanical energy activation effect of mechanical force and the mediating effect of the migration aid. After drying, it is ground and sieved to obtain the product. Based on the above reaction idea, further coordination with the control of various conditions / parameters can achieve better synergy. More importantly, the modified organic composite bentonite obtained by this method has unexpected advantages in the field of iron ore pellets.
[0024] (2) The modified organic composite bentonite prepared by this invention has good binding and adsorption properties. It can also effectively reduce the amount of bentonite used. When the amount of untreated bentonite is 1.5%, the drop strength of green pellets can only reach 4.0 times / (0.5m). Using the modified organic composite bentonite of this invention as a binder to prepare iron ore pellets, the amount of bentonite can be reduced to 1.0%, and the drop strength of green pellets can be increased to 5.0 times / (0.5m). It has important application value in many fields such as adsorption, catalysis, and iron ore pelletizing.
[0025] (3) The preparation process of the present invention is simple, low in cost and environmentally friendly. Attached Figure Description
[0026] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0027] Figure 1 This is a graph showing the effect of different amounts of migration aids on the green pellet strength of iron ore pellets prepared in Examples 1-5 of this invention.
[0028] Figure 2 This is a graph showing the effect of different amounts of migration aids on the strength of oxidized pellets in the modified organic composite bentonite prepared in Examples 1-5 of this invention.
[0029] Figure 3 This is a graph showing the effect of different amounts of migration aids on the physical properties of the modified organic composite bentonite prepared in Examples 1-5 of this invention.
[0030] Figure 4These are scanning electron microscope (SEM) images of the untreated bentonite of this invention and the modified organic composite bentonite prepared in Examples 1-5; wherein, Figure 4 (a) is a scanning electron microscope image of untreated bentonite. Figure 4 (b) is a scanning electron microscope image of the modified organic composite bentonite from Example 1. Figure 4 (c) is a scanning electron microscope image of the modified organic composite bentonite from Example 2. Figure 4 (d) is a scanning electron microscope image of the modified organic composite bentonite of Example 3. Figure 4 (e) is a scanning electron microscope image of the modified organic composite bentonite of Example 4. Figure 4 (f) is a scanning electron microscope image of the modified organic composite bentonite of Example 5;
[0031] Figure 5 X-ray diffraction spectroscopy analysis of the modified organic composite bentonite prepared according to the embodiments of the present invention;
[0032] Figure 6 The present invention relates to the zeta potential analysis of untreated bentonite and modified organic composite bentonite.
[0033] Figure 7 This describes the effect of different types of organic binders on the green pellet performance of the modified organic composite bentonite prepared in Examples 2 and 6-9 of this invention.
[0034] Figure 8 This invention relates to the effect of different types of organic binders on the green ball strength of mechanically modified organic composite bentonite prepared in Comparative Examples 2-6. Detailed Implementation
[0035] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.
[0036] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.
[0037] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.
[0038] This invention addresses existing problems by providing a modified organic composite bentonite, its preparation method, and its application.
[0039] In the following examples, the migration aid specifically used is dimethyl sulfoxide; alcohol refers to 95% ethanol.
[0040] Example 1
[0041] A method for preparing modified organic composite bentonite includes the following steps:
[0042] S1: Mix the migration aid and water, then add humic acid (HA), an organic binder accounting for 1% of the bentonite dosage, and heat to 80°C while stirring until homogeneous.
[0043] S2: Then add it to the bentonite, mix well, and age for 36 hours;
[0044] S3: The mixture was wet-milled using a planetary ball mill for mechanical treatment. The milling time was 30 minutes, and the milling speed was 350 r / min. Alcohol was added as a medium during the wet milling process. After milling, the mixture was dried, ground, and sieved through a 200-mesh sieve to obtain the final product. The migration aid accounted for 2% of the bentonite's mass.
[0045] Example 2
[0046] A method for preparing modified organic composite bentonite includes the following steps:
[0047] S1: Mix the migration aid and water, then add humic acid (HA), an organic binder accounting for 1% of the bentonite dosage, and heat to 80°C while stirring until homogeneous.
[0048] S2: Then add it to the bentonite, mix well, and age for 36 hours;
[0049] S3: The mixture was mechanically treated using a planetary ball mill for 30 minutes at a speed of 350 r / min. Alcohol was added as a medium during wet milling. After milling, the mixture was dried, ground, and sieved through a 200-mesh sieve to obtain the final product. The migration aid accounted for 4% of the bentonite's mass.
[0050] Example 3
[0051] A method for preparing modified organic composite bentonite includes the following steps:
[0052] S1: Mix the migration aid and water, then add humic acid (HA), an organic binder accounting for 1% of the bentonite dosage, and heat to 80°C while stirring until homogeneous.
[0053] S2: Then add it to the bentonite, mix well, and age for 36 hours;
[0054] S3: The mixture was mechanically treated using a planetary ball mill for 30 minutes at a speed of 350 r / min. Alcohol was added as a medium during wet milling. After milling, the mixture was dried, ground, and sieved through a 200-mesh sieve to obtain the final product. The migration aid accounted for 6% of the bentonite's mass.
[0055] Example 4
[0056] A method for preparing modified organic composite bentonite includes the following steps:
[0057] S1: Mix the migration aid and water, then add humic acid (HA), an organic binder accounting for 1% of the bentonite dosage, and heat to 80°C while stirring until homogeneous.
[0058] S2: Then add it to the bentonite, mix well, and age for 36 hours;
[0059] S3: The mixture was mechanically treated using a planetary ball mill for 30 minutes at a speed of 350 r / min. Alcohol was added as a medium during wet milling. After milling, the mixture was dried, ground, and sieved through a 200-mesh sieve to obtain the final product. The migration aid accounted for 8% of the bentonite's mass.
[0060] Example 5
[0061] A method for preparing modified organic composite bentonite includes the following steps:
[0062] S1: Mix the migration aid and water, then add humic acid (HA), an organic binder accounting for 1% of the bentonite dosage, and heat to 80°C while stirring until homogeneous.
[0063] S2: Then add it to the bentonite, mix well, and age for 36 hours;
[0064] S3: The mixture is mechanically treated using a planetary ball mill for 30 minutes at a speed of 350 rpm. Alcohol is added as a medium during wet milling. After milling, the mixture is dried, ground, and sieved through a 200-mesh sieve to obtain the final product. The migration aid accounts for 10% of the bentonite's mass.
[0065] Example 6
[0066] A method for preparing modified organic composite bentonite includes the following steps:
[0067] S1: Mix 4% of the migration aid by weight of bentonite with water, then add 1% of the organic binder by weight of bentonite, heat to 80°C and stir evenly. The organic binder is carboxymethyl cellulose (CMC).
[0068] S2: Then add it to the bentonite, mix well, and age for 36 hours;
[0069] S3: The mixture is mechanically treated using a planetary ball mill. The ball milling time is 30 minutes and the ball milling speed is 350 r / min. Alcohol is added as a medium for wet milling. After ball milling, the mixture is dried, ground, and sieved to obtain the material passing through a 200-mesh sieve.
[0070] Example 7
[0071] A method for preparing modified organic composite bentonite includes the following steps:
[0072] S1: Mix 4% of the migration aid by weight of bentonite with water, then add 1% of the organic binder by weight of bentonite, heat to 80°C and stir evenly. The organic binder is polyacrylamide (PAM).
[0073] S2: Then add it to the bentonite, mix well, and age for 36 hours;
[0074] S3: The mixture is mechanically treated using a planetary ball mill. The ball milling time is 30 minutes and the ball milling speed is 350 r / min. Alcohol is added as a medium for wet milling. After ball milling, the mixture is dried, ground, and sieved to obtain the material passing through a 200-mesh sieve.
[0075] Example 8
[0076] A method for preparing modified organic composite bentonite includes the following steps:
[0077] S1: Mix 4% of the migration aid by weight of bentonite with water, then add 1% of the organic binder by weight of bentonite, heat to 80°C and stir evenly. The organic binder is carboxymethyl starch (CMS).
[0078] S2: Then add it to the bentonite, mix well, and age for 36 hours;
[0079] S3: The mixture is mechanically treated using a planetary ball mill. The ball milling time is 30 minutes and the ball milling speed is 350 r / min. Alcohol is added as a medium for wet milling. After ball milling, the mixture is dried, ground, and sieved to obtain the material passing through a 200-mesh sieve.
[0080] Example 9
[0081] A method for preparing modified organic composite bentonite includes the following steps:
[0082] S1: Mix 4% of the migration aid by weight of bentonite with water, then add 1% of the organic binder by weight of bentonite, heat to 80°C and stir evenly. The organic binder is polyvinyl chloride (PVC).
[0083] S2: Then add it to the bentonite, mix well, and age for 36 hours;
[0084] S3: The mixture is mechanically treated using a planetary ball mill. The ball milling time is 30 minutes and the ball milling speed is 350 r / min. Alcohol is added as a medium for wet milling. After ball milling, the mixture is dried, ground, and sieved to obtain the material passing through a 200-mesh sieve.
[0085] Comparative Example 1
[0086] The preparation process is the same as in Example 1, except that the amount of migration aid added accounts for 15% of the mass of bentonite. Furthermore, when the prepared mechanically modified organic composite bentonite is used to produce iron ore pellets, under appropriate dosage, the green pellet drop and compressive strength are significantly improved, but the green pellet bursting temperature drops below 400℃, making it difficult to meet pellet production standards.
[0087] Comparative Example 2
[0088] The preparation process is the same as in Example 1, except that no migration aids are added.
[0089] Comparative Example 3
[0090] The preparation process is the same as in Example 6, except that no migration aids are added.
[0091] Comparative Example 4
[0092] The preparation process is the same as in Example 7, except that no migration aids are added.
[0093] Comparative Example 5
[0094] The preparation process is the same as in Example 8, except that no migration aid is added.
[0095] Comparative Example 6
[0096] The preparation process is the same as in Example 9, except that no migration aids are added.
[0097] application
[0098] The compressive strength of green pellets reflects their ability to withstand the weight and compression of the material layer during transport and stacking. Each green pellet is placed on a compressive strength index tester and pressurized until it breaks. The average value of the maximum force on 20 green pellet samples is taken as the green pellet compressive strength index, denoted as N / P. Green pellet drop strength is an important indicator of the impact capacity of green pellets during transport and is also the basis for the permissible number of green pellet rotations in pellet plant design. Each green pellet is repeatedly dropped from a height of 500mm onto a 10mm thick steel plate until it breaks. The average number of drops without breaking is taken as the calcined green pellet drop strength index, denoted as drops / (0.5m). The minimum requirement is typically ≥4 drops / (0.5m). The green pellet bursting temperature refers to the highest temperature that green pellets can withstand without cracking or bursting. Under fixed empty tower flow rate and variable temperature conditions, green pellet samples (50 pellets per group) are continuously replaced until the number of broken pellets in that group reaches 10% of the total number. This temperature is the green pellet bursting temperature of roasted pellets, denoted as °C. The compressive strength of preheated and roasted pellets characterizes the mechanical properties of the pellets. Pellets are placed on a pellet compressive strength index tester and pressurized until they burst. The average value of the maximum force on 20 pellet samples is taken as the compressive strength index of the preheated and roasted pellets, denoted as N / P.
[0099] The swelling performance of bentonite is expressed as its swelling volume. The volume of 1g of bentonite after swelling in dilute hydrochloric acid solution for 24 hours is called the swelling volume, denoted as mL / g. The colloidal value of bentonite reflects the degree of particle dispersion and hydration. The colloidal value is the volume of 15g of bentonite mixed with 100mL of water, then 1g of magnesium oxide added. After complete dispersion and standing for 24 hours, the volume of the gel formed is called the colloidal value, denoted as mL / 15g. The swelling volume and colloidal value of bentonite reflect its good dispersion, hydrophilicity, and swelling properties; higher values indicate superior performance.
[0100] from Figure 1 It can be seen that as the amount of migration aid increases, the drop strength and compressive strength of green balls gradually increase. The soluble components of the migration aid cause the hydrophilic groups in the organic binder to diffuse to the surface of the bentonite particles. The modified organic composite bentonite filling the iron ore particles significantly improves the hydrophilicity of the iron ore particle surface and effectively enhances the adhesion of the organic modified composite bentonite.
[0101] from Figure 2 It can be seen that with the increase of the amount of migration aid, the compressive strength of both preheated pellets and calcined pellets shows an upward trend, and under the condition of adding an appropriate amount of migration aid, both can meet the strength requirements of oxidized pellets.
[0102] from Figure 3It can be seen that as the amount of migration aid increases, the hydrophilic groups of the organic binder are effectively activated, and a large number of -COO- adsorbed on the montmorillonite matrix and end face, enhancing the ability to attract polar water molecules, thereby improving the dispersion performance of bentonite. The colloidal value and swelling ratio of the modified bentonite both show an upward trend.
[0103] Figure 4 These are scanning electron microscope (SEM) images of the untreated bentonite of this invention and the modified organic composite bentonite prepared in Examples 1-5; wherein, Figure 4 (a) is a scanning electron microscope image of untreated bentonite. Figure 4 (b) is a scanning electron microscope image of the modified organic composite bentonite from Example 1. Figure 4 (c) is a scanning electron microscope image of the modified organic composite bentonite from Example 2. Figure 4 (d) is a scanning electron microscope image of the modified organic composite bentonite of Example 3. Figure 4 (e) is a scanning electron microscope image of the modified organic composite bentonite of Example 4. Figure 4 (f) is a scanning electron microscope image of the modified organic composite bentonite of Example 5;
[0104] Figure 5 The modified organic composite bentonite prepared in the embodiments of the present invention is shown by X-ray diffraction spectroscopy analysis. The main phases of the modified organic composite bentonite are still montmorillonite, quartz and calcite. The diffraction peak of montmorillonite does not change significantly, indicating that the migration aid is loaded on montmorillonite in the form of coating.
[0105] Figure 6 This invention relates to the Zeta potential analysis of untreated bentonite and modified organic composite bentonite. The modified organic composite bentonite exhibits lower electronegativity, and the negative surface potential of the bentonite increases with increasing pH, indicating that the organic composite modified bentonite suspension is more stable in alkaline aqueous solutions. The results show that mechanical force increases the active sites for adsorption of the organic binder on the montmorillonite surface, and the migration aid containing -S=O- functional groups forms hydrogen bonds with the Al-OH groups contained in the bentonite. This synergistically enhances the negative surface potential of the modified organic composite bentonite.
[0106] Figure 7 This paper examines the influence of the type of organic binder used in Examples 2 and 6-9 of the present invention on the green pellet performance. The results show that, under the condition of controlling the same amount of composite pellet binder, the addition of migration aids during mechanical modification, and the organic binders humic acid (HA), carboxymethyl cellulose (CMC), polyacrylamide (PAM), carboxymethyl starch (CMS), and polyvinyl chloride (PVC) have a significant effect on improving the green pellet performance. This indicates that the addition of migration aids can synergistically work with mechanical modification to further improve the modification effect of bentonite.
[0107] Figure 8This invention relates to the effects of the type of organic binder on green pellet strength in Comparative Examples 2-6 without the addition of migration aids. The results show that, under the condition of controlling the same amount of composite pellet binder, organic binders such as humic acid (HA), carboxymethyl cellulose (CMC), polyacrylamide (PAM), carboxymethyl starch (CMS), and polyvinyl chloride (PVC) can also improve the green pellet performance of the pellets through mechanical modification alone. However, compared with the synergistic modification of migration aids and mechanical force, the modification effect of bentonite is poor.
[0108] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing modified organic composite bentonite, characterized in that, Includes the following steps: S1: Mix the migration aid with water and stir, then add the organic binder, heat and disperse evenly to obtain a mixed solution; S2: Add the mixed solution to bentonite and mix well to obtain a mixture, then carry out an aging reaction; S3: The mixture after the reaction is subjected to wet ball milling, then dried, ground, and sieved to obtain the final product; The migration aid is dimethyl sulfoxide; the organic binder is at least one of humic acid, carboxymethyl cellulose, polyacrylamide, carboxymethyl starch, and polyvinyl chloride; the migration aid accounts for 0.01~12% of the mass of bentonite; the organic binder accounts for 0.1~10% of the mass of bentonite; the mass ratio of the migration aid to water is 0.5~1.
0. The wet ball milling process specifically involves using a planetary ball mill with 95% ethanol as the medium for wet ball milling; the wet ball milling time is 20~30 min, and the wet ball milling speed is 300~400 r / min; the sieving process specifically involves passing the material through a 200 mesh sieve and collecting the material that passes through the sieve.
2. The method for preparing modified organic composite bentonite according to claim 1, characterized in that, In step S1, the heating temperature is 80 ℃.
3. The method for preparing modified organic composite bentonite according to claim 1, characterized in that, In step S2, the aging reaction time is 24~36 h.
4. A modified organic composite bentonite obtained by the preparation method according to any one of claims 1 to 3.
5. The application of a modified organic composite bentonite obtained by the preparation method according to any one of claims 1 to 3 or the modified organic composite bentonite according to claim 4 in iron ore pellets.
Citation Information
Patent Citations
Preparation method and application of high-water-absorptivity composite binder for iron ore pellets
CN105087915A
Method for manufacturing modified-bentonite and modified-bentonite
KR101048436B1